Beyond keto : [burn fat, heal your gut, and reverse disease with a Mediterranean-keto lifestyle] - Colbert, Don (Siloam, 2022)
New York Times best-selling author Don Colbert, MD, has created a new dietary lifestyle, the Beyond Keto lifestyle. Beyond Keto blends the best of both worlds, the Ketogenic and Mediterranean diets, and combines them with cutting-edge research on gut health. The key is eliminating foods that cause inflammation. If you've tried a conventional Ketogenic or Mediterranean diet and still feel bloated, sluggish, or your weight loss has plateaued, Beyond Keto gives you the guidelines to go deeper in a low carb/anti-inflammatory lifestyle that empowers your body.--